AB0166 Sex-Specific Gene Expression Differences in Oligoarticular Juvenile Idiopathic Arthritis. (15th July 2016) - Chiaroni-Clarke, R.C.; Chavez, R.A.; Munro, J.E.; Allen, R.C.; Akikusa, J.D.; Oshlack, A.; Maksimovic, J.; Ponsonby, A.-L.; Saffery, R.; Ellis, J.A.
Abstract : Background: Juvenile idiopathic arthritis (JIA) is a paediatric autoimmune disease (AD) with a female preponderance, though this differs by subtype. Whether this sex bias is reflective of differing disease pathogenesis between the sexes is unknown. Gene expression signatures can be biologically and clinically informative, but few expression studies have been performed in JIA. Though gene expression is recognised as sexually dimorphic in many states, its role in JIA sex bias has not been considered. In response to infection females produce more antibodies than males, which could increase natural autoantibody production and the risk of developing AD. Gene expression differences between the sexes may reflect this. The reduced heterogeneity afforded by sex-stratified transcriptome-wide analysis may provide insight into how sex influences disease pathogenesis in JIA. Objectives: We aimed to identify sex-specific differences in patients with oligoarticular JIA versus healthy controls through RNA-seq analysis on CD4+ T cells. Methods: Six male and six female oligoarticular JIA cases, with no prior exposure to disease-modifying anti-rheumatic drugs, were age and sex-matched to healthy controls. CD4+ T cells were selected as existing data links T cell gene networks to JIA. RNA was extracted from CD4+ T cells using the Qiagen miRNeasy extraction kit. Sequencing library preparation was performed using the Illumina TruSeq Stranded Total RNA LT kit. One female sample did not pass quality control and was not sequenced. Sequencing was performed using 75bp paired-end reads to a depth of ∼20 million reads on the Illumina NextSeq. Quality trimmed reads were mapped to the genome using the STAR aligner. Read counts across exons and genes were summarised using featureCounts. Normalised read counts were used for differential gene expression analysis with edgeR. GOseq was used for gene ontology analysis. Males and females were analysed separately. Results: No sex-specific differentially expressed (DE) genes reached FDR adjusted p<0.05. At unadjusted p<0.05 there were far more male (1480) than female (118) specific DE genes, with 24 overlapping. Pathway analysis of male-specific DE genes highlighted antigen processing and presentation, immune response, and IFNΥ production, among other disease-relevant gene networks. Corresponding female-specific analysis did not reveal obvious disease-relevant networks. For many genes DE between male cases and controls, male case gene expression appeared more similar to all females (Figure 1 ). Conclusions: We have identified sex-specific differences in CD4+ T cell gene expression between healthy controls and oligoarticular JIA cases predominantly in males, despite the female preponderance. Our data may reflect that some of the pathogenesis for JIA differs between the sexes, and that gene expression differences play a particularly important role in male JIA, perhaps by a more "female" immune response occurring in male cases. Given the small sample size, replication is necessary and is underway. Disclosure of Interest: None declared